2017
DOI: 10.1093/nar/gkx1046
|View full text |Cite
|
Sign up to set email alerts
|

The RNA processing factors THRAP3 and BCLAF1 promote the DNA damage response through selective mRNA splicing and nuclear export

Abstract: AbstractmRNA splicing and export plays a key role in the regulation of gene expression, with recent evidence suggesting an additional layer of regulation of gene expression and cellular function through the selective splicing and export of genes within specific pathways. Here we describe a role for the RNA processing factors THRAP3 and BCLAF1 in the regulation of the cellular DNA damage response (DDR) pathway, a key pathway involved in the maintenance of genomic stability and the prevention of oncogenic transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
89
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 36 publications
4
89
0
Order By: Relevance
“…Treatment with cisplatin, mitomycin C, irinotecan, doxorubicin, etoposide and 5-FU, all resulted in cytosolic dsDNA ( Figure 1B). Quantification using a previously described image compartmentalisation and quantification algorithm [13], confirmed that cytosolic dsDNA significantly increased following treatment with cisplatin, mitomycin C, irinotecan, doxorubicin, etoposide and 5-FU, in comparison to vehicle treated control cells ( Figure 1C). dsDNAse treatment was used as a control to confirm quantified fluorescence signal was dsDNA (***=p≤0.001).…”
Section: Inhibition Of Topoisomerase I and Ii Strongly Induces Cxcl10supporting
confidence: 60%
“…Treatment with cisplatin, mitomycin C, irinotecan, doxorubicin, etoposide and 5-FU, all resulted in cytosolic dsDNA ( Figure 1B). Quantification using a previously described image compartmentalisation and quantification algorithm [13], confirmed that cytosolic dsDNA significantly increased following treatment with cisplatin, mitomycin C, irinotecan, doxorubicin, etoposide and 5-FU, in comparison to vehicle treated control cells ( Figure 1C). dsDNAse treatment was used as a control to confirm quantified fluorescence signal was dsDNA (***=p≤0.001).…”
Section: Inhibition Of Topoisomerase I and Ii Strongly Induces Cxcl10supporting
confidence: 60%
“…The resulting combinations likely provide surfaces that facilitate binding to RNA/DNA hybrids. Other protein complexes include RPA1, RNase H1 (Nguyen et al 2017), and THRAP3/BCLAF1 (Vohhodina et al 2017). Thus, our pull-down assays identify direct RNA-protein and indirect RNA-protein interactions mediated by protein-protein interactions.…”
Section: Resultsmentioning
confidence: 87%
“…( ) In vitro studies also implicated Bclaf1 in pathways linking transcriptional events to cell death, DNA damage, or autophagy. ( ) Although most studies suggest that Bclaf1 acts as a tumor suppressor, more‐recent studies provided evidence for an oncogenic function of Bclaf1 in bladder and colon cancer. ( ) Thus, the function of Bclaf1 in carcinogenesis is controversial and still needs to be further explored in different tumor tissues.…”
mentioning
confidence: 99%